PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA KARYAWAN SUZUYA MALL BIREUEN - Bariah, Chaerul; SE, Aprimana (JURNAL KEBANGSAAN, 2019)
This study examines the impact of directors compensation, capital structure, and diversification on company performance. The sample of this research was 20 listed firms on Indonesia Stock Exchange from 2013 to 2016 and taken using purposive sampling technique. The method of data analysis was multiple linear regression analysis. The results shows that directors compensation and capital structure influenced firms performance. The diversification not influenced firms performance. The further research should expand the research subject and should use the other subjects, such as service industry, property industry, and finance industry in order to make the sample more representative. Keywords: Directors Compensation, Capital Structure, Diversification, Performance.